The effect of ethnicity on prescribing practice and treatment outcome in inpatients suffering from schizophrenia in Greece - Christodoulou Christos; Rizos Emmanouil N; Seretis Dionisios; Apostolopoulos Athanassios; Douzenis Athanassios; Lykouras Lefteris (BMC Psychiatry, 2011)
Abstract Background No studies have been conducted in Greece with the aim of investigating the influence of ethnicity on the prescribing and treatment outcome of voluntarily admitted inpatients. Most studies conducted in the UK and the US, both on inpatients and outpatients, focus on the dosage of antipsychotics for schizophrenic patients and many suffer from significant methodological limitations. Using a simple design, we aimed to assess negative ethnic bias in psychotropic medication prescribing by comparing discrepancies in use between native and non-native psychiatric inpatients. We also aimed to compare differences in treatment outcome between the two groups. Methods In this retrospective study, the prescribing of medication was compared between 90 Greek and 63 non-Greek inpatients which were consecutively admitted into the emergency department of a hospital covering Athens, the capital of Greece. Participants suferred from schizophrenia and other psychotic disorders. Overall, groups were compared with regard to 12 outcomes, six related to prescribing and six related to treatment outcome as assesed by standardised psychometric tools. Results No difference between the two ethnic groups was found in terms of improvement in treatment as measured by GAF and BPRS-E. Polypharmacy, use of first generation antipsychotics, second generation antipsychotics and use of mood stabilizers were not found to be associated with ethnicity. However, non-Greeks were less likely to receive SSRIs-SNRIs and more likely to receive benzodiazepines. Conclusions Our study found limited evidence for ethnic bias. The stronger indication for racial bias was found in benzodiazepine prescribing. We discuss alternative explanations and give arguments calling for future research that will focus on disorders other than schizophrenia and studying non-inpatient populations.